Music a very short introduction - Cook, Nicholas 1950- (Oxford University Press, 2000)
This 'Very Short Introduction' to music draws on a number of accessible examples, and prompts us to call on our own personal musical experiences in order to think more critically about issues such as the roles of the performer and the listener
Originally published: 1998. - Includes bibliographical references and index
Keywords: Geschichte; Music; Music appreciation; Musikästhetik; Musik; Einführung